Uptake of a dashboard designed to give realtime feedback to a sentinel network about key data required for influenza vaccine effectiveness studies - Pathirannehelage, S; Kumarapeli, P; Byford, R; Yonova, I; Ferreira, F; de Lusignan, S (IOS Press, 2019)
Dashboards are technologies that bringing together a range of data sources for observational or analytical purposes. We have created a customised dashboard that includes all the key data elements required for monitoring flu vaccine effectiveness (FVE). This delivers a unique dashboard for each primary care provider (general practice) providing data to the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC), one of the oldest European surveillance systems. These FVE studies use a test negative case control (TNCC) design. TNCC requires knowledge of practice denominator; vaccine exposure, and results of influenza virology swabs carried out to identify in an influenza-like-illness (ILI), a clinical diagnosis, really is influenza. The dashboard displays the denominator uploaded each week into the surveillance system, compared with the nationally known practice size (providing face-validity for the denominator); it identifies those exposed to the vaccine (by age group and risk category) and virology specimens taken and missed opportunities for surveillance (again by category). All sentinel practices can access in near real time (4 working days in areas) their rates of vaccine exposure and swabs conducted. Initial feedback is positive; 80% (32/40) practices responded positively.